LoRA-LoRaWAN Communication Multinode for 3D Localization in Coastal Environment - Musayyanah, Musayyanah; Pauladie Susanto; Pradita Maulidya Efendi; Charisma Dimas Affandi; Kristin Lebdaningrum; Theodorus Visser Inulima (Jurusan Teknik Elektromedik, Politeknik Kesehatan Kemenkes Surabaya, Indonesia, 2025)
The application of LoRAWAN on Internet of Things (IoT) technology is to communicate in real time and accommodate data from many nodes based on device addresses. LoRAWAN device communication is able to reach distances of up to kilometers with low cost, compared to high-frequency cellular communication currently installed on the coast. This application can be done on LoRA devices to forward the results of three-dimensional localization based on signal strength. This research was to conduct three-dimensional localization based on signal strength from three LoRa End Nodes (EN) to four LoRa Anchor Nodes (AN), then forwarded to the server to be displayed on the Datacakes application. Localization begins with a path loss model analysis to determine the path loss coefficient. The localization results were in the form of data packets consisting of longitude, latitude, and altitude position parameters and the results of the EN to AN distance conversion. The data packet was forwarded to the The Things Networks (TNN) server with Over The Air Activation (OTAA) activation mode. Root Mean Square Error (RMSE) analysis of the localization results for EN1 was 169.35 meters, EN2 was 395.08 meters and EN3 was 183.24 meters. The localization data packets were forwarded to the cloud server via the GW device. Analysis of GW communication with EN is shown by the Packet Error Ratio (PER), Air Time (AT), and latency parameters. The smallest PER results, fastest AT and lowest latency were obtained from GW communication with EN2, where the position of EN2 was closest to GW among the other ENs.